Singapore Perspectives 2010 : Home. Heart. Horizon. - How, Tan Tarn (World Scientific, 2010)
"The Singapore Perspectives" series is a yearly publication that provides critical analysis of emerging trends and issues Singapore faces in terms of social, economic and political development. It is a quick and essential reference for understanding the broad policy discussions that animate thought leaders, policy-makers and the public in the country during the immediate period or that are likely to do so in the short and medium term. In this volume, contributors look at the short-term challenges that Singapore faces and the policy options open to the nation, and share their insights.